Intellectual capital on financial performance in sharia banks in Indonesia - Rizkyanti, Ratih; Isnurhadi, Isnurhadi; Andriana, Isni; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2020)
This research was conducted to determine the effect of intellectual capital (VACA,VAHU, STVA) on the financial performance of Islamic banks in Indonesia. The population in this study were all 14 Islamic commercial banks in Indonesia. The sample used in this study met the criteria of 12 Islamic commercial banks using a purposive sampling technique. The data collection method uses secondary data in the financial statements for the period 2014-2019. The results of the multiple linear regression analysis show that value-added capital employees (VACA) have a positive and significant effect on the financial performance of Islamic banks in Indonesia for the period 2014-2019. Value-added human capital (VAHU) has a negative and significant effect on financial performance in Islamic banks in Indonesia, Indonesia for the period 2014-2019. Structural capital value-added (STVA) has a positive and significant effect on financial performance at Islamic banks in Indonesia for the period 2014-2019. Intellectual capital in banking companies can be used as a tool to increase company value so that it can continue to compete and can develop IC as a tool to increase company value so that it can continue to compete and become better.